2010
DOI: 10.1007/s00441-010-1098-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lymphatic endothelium-specific hyaluronan receptor LYVE-1 in the developing mouse kidney

Abstract: Our knowledge of the embryonic development of the lymphatic vessels within the kidney is limited. The aim of this study was to establish the time of appearance and the distribution of intra-renal lymphatic vessels in the developing mouse kidney by using the lymphatic marker, LYVE-1. Kidneys from embryonic day 12 (E12) to E18, from neonates at post-natal day 1 (P1) to P21, and from adults were studied. In the adult mouse kidney, LYVE-1 was expressed mainly in the lymphatic endothelial cells (LECs) and in a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
46
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 51 publications
10
46
1
Order By: Relevance
“…Noteworthy, the expression of hyaluronidases there was restricted to macrophages but not reticular cells. Ultrastructually, LYVE-1 is always localized in the plasma membrane but not in the cytoplasm and cell organelle, in contrast to its cytoplasmic localization in macrophagic cells, such as intracellular vesicles and vacuoles (21,41). The dual membrane localization of LYVE-1 in the vascular endothelial cells is in agreement with early observations concerning LYVE-1 in the endothelium of lymphatics (29), suggesting transport via the cells (transcytosis) without intracellular degradation.…”
Section: Topographical and Functional Relationship Between Lyve-1-expsupporting
confidence: 79%
See 1 more Smart Citation
“…Noteworthy, the expression of hyaluronidases there was restricted to macrophages but not reticular cells. Ultrastructually, LYVE-1 is always localized in the plasma membrane but not in the cytoplasm and cell organelle, in contrast to its cytoplasmic localization in macrophagic cells, such as intracellular vesicles and vacuoles (21,41). The dual membrane localization of LYVE-1 in the vascular endothelial cells is in agreement with early observations concerning LYVE-1 in the endothelium of lymphatics (29), suggesting transport via the cells (transcytosis) without intracellular degradation.…”
Section: Topographical and Functional Relationship Between Lyve-1-expsupporting
confidence: 79%
“…LYVE-1 has been believed to be a hyaluronan receptor molecule abundantly expressed in the endothelium of lymphatic vessels, with additional expressions in sinusoidal endothelia of the liver, lymph node, and spleen and in some macrophage lineages (1,3,21,26,41). However, we found a broader distribution of LYVE-1: vascular endothelial cells in the lung, adrenal gland, and endocardium.…”
Section: Lyve-1 Is a Novel Marker For The Reticulo-endothelial Systemcontrasting
confidence: 53%
“…Previous studies have shown that lymphatic ECs start to appear in the mouse kidney at E13.5 40 and that multiple cell types contribute to the their development, including venous derived ECs, mesenchymal cells, and hematopoietic cells. 41 ;R26 LacZ/+ mice suggests a distinct origin of lymphatic ECs from non-SCL+ precursors.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study on kidney in mouse embryos identifies the Lyve-1-positive cells as possessing F4/80 þ / CD11b À (macrophage/dendritic) antigen (Lee et al, 2011). These doublepositive cells were found to form part of the lymphatic vascular wall of the developing kidney.…”
Section: Developmental Dynamicsmentioning
confidence: 94%